Pelatihan Pengoperasian Drone sebagai Peningkatan Kemampuan Kompetensi SMK Perikanan Tukak Sadai Bangka Selatan - Umroh, Umroh; Hudatwi, Mu’alimah; Wahidin, La Ode; Pamungkas, Aditya; Akhriati, Irma; Utami, Eva (LPPM Universitas Trunojoyo Madura, 2024)
SMKN 1 Tukak is the vocational school in the field of fisheries in South Bangka Regency. Some training is really needed to increase the competency of SMK students, so that training is carried out that can improve students' abilities. One of the trainings is mapping using drones, because spatial data is needed in the fields of fisheries, agriculture, mining. The objectives of the activity: 1) provide students with an understanding of Drone Mapping knowledge, 2) increase the competency of SMK students related to mapping. Stages of activity: 1) training on spatial data collection using drones, 2) training on spatial data processing from drones, 3) training on introductory mapping, and 4) socialization of drone map results. The training participants were made into 3 groups according to class XI majors, namely: Brackish Water and Marine Agribusiness (APAPL), Fishing Vessel Nautics (NKPI), and Fishery Products Processing Agribusiness (APHPL). Each group was accompanied by a trainer from Bangka Belitung University. The process of learning to take aerial photos using drones is taught directly, starting from installation, drone flight and downloading aerial photos. Installed apps include DJI Go, Control DJI and Pix4D. The application is used for taking aerial photos using drones. Each group from the PBAPL, APHP, NKPI majors carried out drone flights and took aerial photos according to the trainer's instructions. The results of the aerial photos taken by each group were used to make aerial photo maps and contour maps. The enthusiasm of the students of SMKN 1 Tukak in PMTJ 2023 activities was very high. This is indicated by the active participation of the participants in making flight missions and flying drones as well as processing spatial data.